The Use of the Catalysts Based on Coal Ash Microsphere and Chrysotile in the Thermal Destruction of Primary Coal Tar - Aitbekova, D.E.; Baikenov, M.I.; Muratbekova, A.A.; Bolatbay, A.N.; Balpanova, N.Zh.; Tyanakh, S.; Ma, F.; Khamitova, T.O. (Karagandy University of the name of academician E.A. Buketov, 2024)
In order to evaluate the possibility of using different catalysts prepared for the hydrogenation process of primary coal tar, the method of differential thermal analysis was used, which allows to determine the kinetic parameters of thermal destruction, such as the rate constant, activation energy, and pre-exponential multiplier. The effect of catalysts on characteristics of mass loss during heating of “Shubarkol Komir” JSC primary coal tar at a constant speed (20 K/min) in a nitrogen medium has been considered. Microsphere, NiO/microsphere, CoO/microsphere, chrysotile and NiCo/chrysotile have been taken as catalytic additives. In the presence of the catalysts, the rate of thermal destruction of primary coal tar increases in the following order: CoO/microsphere < NiO/microsphere < NiCo/chrysotile. While microsphere catalysts extend the range of thermal destruction, chrysotile catalysts lead to the rapid completion of the destruction process. This fact is characterized by the formation of bonds between catalytic additives and primary coal tar. It is important to determine such parameters that affect on the activation energy and macrokinetics of the thermal decomposition process for prediction of catalyst activity during hydrogenation of heavy hydrocarbon raw materials.
Keywords: primary coal tar; differential thermal analysis; catalyst; hydrogenation; microsphere; chrysotile; nickel; cobalt